Clinical and Biochemical Profile of Children with Chronic Kidney Disease in a Tertiary Care Hospital of Bangladesh - Yasmin, Farhana; Afroz, Shireen; Ferdous, Tahmina; Tanjila, Umme; Baroi, Sukriti (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Background: Chronic kidney disease (CKD) is an insidious and irreversible condition that eventually progresses to end stage renal failure and important cause of morbidity and mortality in children worldwide. However, the care of these patients represents a challenge for health care providers, which must pay attention not only to renal disease, but also to the various extra renal manifestations that affect growth and development. Evaluation of clinical and biochemical profile of children with chronic kidney disease can help to meet up this challenge. Methods: This cross-sectional observational cohort study evaluated clinical, anthropometric and biochemical variables of children with chronic kidney disease aged 2 to 16 years in the department of Pediatric Nephrology, Dhaka Shishu (Children) Hospital, Bangladesh, during July’ 2018 to December’ 2018. A total of thirty-six children with chronic kidney disease with creatinine clearance <60ml/min/1.73 m2 and on supportive treatment and haemodialysis were included. In control group, equal number of age and sex matched healthy children without any preexisting chronic diseases were included. Both study group and control group were assessed for sociodemographic data, nutritional status, clinical and biochemical parameters. Results: The mean age was 9.09±3.01 years in case group and 7.85±3.69 years in control group. In case group, 22 patients (61.1%) were male and 14 (38.9%) were female and the ratio was 1.5:1. In this study we found that a statistically significant decrease in Z-score for (Weight, Height and Body Mass Index) in the CKD patients’ group than control. In terms of blood pressure, 66.7% of patients in the cases group were hypertensive (P = 0.001). There was no significant difference of hypertension among CKD stages in this study. CKD Patients were found anemic with significant decrease in hemoglobin level. Anemia found in 35 patients (97.2%) in the case group than control (P=0.001). CKD stage 5 children had significantly lower hemoglobin level. Serum phosphate and potassium were significantly higher while serum calcium was significantly lower and parathyroid level was higher in case group than control. Conclusion: The present study stated that CKD patients had significantly lower BMI and hemoglobin but hypertensive in comparison to case group. Serum potassium, phosphate and parathyroid higher but serum calcium level was lower in case group. J Bangladesh Coll Phys Surg 2023; 41: 120-125